THE ROLE OF HUMAN RESOURCE MANAGEMENT IN SUPPORTING A SUSTAINABLE ECONOMY - Kadeni Kadeni (Adisam Publisher, 2025)
Human Resource Management (HRM) plays an essential role in driving a sustainable economy through the integration of green practices and sustainability in organisational strategies. By providing training and skills development for employees, HR management increases awareness and the ability to adopt more efficient and environmentally responsible technologies and practices, contributing to the reduction of the company's carbon footprint and operational efficiency. In addition, HR management serves as a driver in creating a sustainability-based work culture by engaging all employees in green initiatives and encouraging cross-functional collaboration. Through policies that support sustainability and reward innovation, HR management ensures that all levels of the organisation are aligned with sustainability goals, helping the company gain a competitive advantage in a market that increasingly values ethical and sustainable business.